“Functionally” Univentricular Hearts: Impact of Pre-Natal Diagnosis - Corno, Antonio Francesco (Frontiers in Pediatrics, 2015)
Within the last few decades the pre-natal echocardiographic diagnosis of congenital heart defects has made substantial progresses, particularly for the identification of complex malformation. “Functionally” univentricular hearts categorize a huge variety of heart malformations. Since no one of the patients with these congenital heart defects can ever undergo a bi-ventricular type of repair, early recognition and decision-making from the neonatal period are required in order to allow for appropriate multiple-step diagnostic and treatment procedures, either of interventional cardiology and/or surgery, on the pathway of “univentricular” heart. In the literature strong disagreements exist about the potential impact of the pre-natal diagnosis on the early and late outcomes of complex congenital heart defects. This review of the recent reports has been undertaken to better understand the impact of pre-natal diagnosis in “functionally” univentricular hearts taking into consideration the following topics: • pre-natal screening • outcomes and survival • general morbidity • neurologic and developmental consequences • pregnancy management and delivery planning • resources utilization and costs/benefits issues • ethical implications, parents counseling, interruption of pregnancy versus treatment